The Influence of the Migration of the Governor’s Subjects from Kalmyk Khanate to China on the Kalmyk Settlements of Orenburg Province in 1771 - Stepan V. Dzhundzhuzov (Монголоведение)
Introduction. The article deals with the problem of the influence of the migration of Kalmyks from Russia to China on the Kalmyk population of Orenburg province in 1771, which is not affected in historiography. The sources for the study were the materials of the fund No. 3 “Orenburg Provincial Chancellery” of the United State Archive of the Orenburg region. Along with the documents containing the orders of the Orenburg governor I.A. Reinsdorp and various reports addressed to him, they contain the testimony of Kalmyks who were interrogated in the office of the Yaik Cossack army. Most archival documents are being introduced into scientific circulation for the first time. The restoration of the outline of the events under consideration through the use of archival materials required the use of special methods of historical research: critical analysis of historical sources, historical continuity, as well as historical-comparative and historical-legal methods that allow tracing common and distinct features in the legal situation of Kalmyk villagers in Orenburg province. Results. Kalmyks-Cossacks of the Yaik army turned out to be directly involved in the process of Kalmyk migration. They were related to the subjects of the governor of the Kalmyk Khanate by kinship and confessional ties. Under the influence of agitation, coercion, or out of fear of parting with their family, some of the Yaik Kalmyks joined the migration provoked by the Kalmyk nobility. However, among the Yaik Kalmyks there were those who not only did not want to leave Russia, but also helped to pursue the fugitives. The efforts of the Russian administration to limit contacts between Orenburg and Stavropol baptized Kalmyks did not allow them to be involved in the migration flow. Moreover, the Stavropol Kalmyk army was replenished by a group of Kalmyks who refused to escape and expressed a desire to become Orthodox Christians.